Examining the President's 2024 Election Strategy through Weberian Conflict Theory - Holqi, Fikri Gali Fernando; Zulfa, Arinda Maulidya (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2024)
As Head of State, a President has a very vital role in efforts to maintain state sovereignty. However, in the 2024 general election in Indonesia, the President reaped negative sentiments identified as the term "Dynastic Politics," which could potentially damage the democratic system. This research is oriented toward identifying and analyzing the President's political leadership strategy in the 2024 election by implementing Weberian conflict theory. Actualize the qualitative description approach with the type of literature study. The data collected will be understood, recorded, and analyzed using Weberian conflict theory. Then, conclusions can be drawn with deductive patterns. The study results stated that charismatic leaders in this regard are more than just fixated on traditional principles of authority, as Weber argues. But also charismatic leaders who are on formal legal authority (President). The President, in this case, carries out a political strategy to form a political dynasty by using the existence of his charismatic leadership. By maintaining legitimacy rather than democratic principles, this strategy will continue to create conflicts with negative implications for charismatic leaders.